2012
DOI: 10.1590/s0006-87052012000100019
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the probabilistic definition of drought: strengths, limitations and an agrometeorological adaptation

Abstract: Drought is a slow-moving hazard that occurs in virtually all countries of the world. In the light of this, several indices have been developed to improve the detection of drought's onset, as well as quantifying other features of this phenomenon. The Standardized Precipitation Index (SPI) is often used in order to characterize meteorological droughts. In addition, this index is largely used by Brazilian's agricultural institutions. In order to add important information to the drought literature, this review art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 41 publications
(53 reference statements)
0
33
0
Order By: Relevance
“…After evaluating the results depicted in Figure 1, it becomes worth emphasizing that the analysis of the SPI literature revels that virtually all studies use a single distribution (frequently the 2-parameter gamma) to calculate this drought index (Guttman, 1999;Wu et al, 2007;Lopez-Moreno & Vicente-Serrano, 2008;Blain 2012;Dutra et al, 2013; among many others). In other words, the use of the SPI has been based on the assumption that, for a given location, a single distribution is always capable of fitting the rainfall amounts summed over several timescales.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After evaluating the results depicted in Figure 1, it becomes worth emphasizing that the analysis of the SPI literature revels that virtually all studies use a single distribution (frequently the 2-parameter gamma) to calculate this drought index (Guttman, 1999;Wu et al, 2007;Lopez-Moreno & Vicente-Serrano, 2008;Blain 2012;Dutra et al, 2013; among many others). In other words, the use of the SPI has been based on the assumption that, for a given location, a single distribution is always capable of fitting the rainfall amounts summed over several timescales.…”
Section: Resultsmentioning
confidence: 99%
“…The normality tests have revealed that the median of the SPI values calculated from generalized normal distribution fall more often within the [-0.05:+0.05] interval than the median of the SPI values obtained from the other distributions. Naturally, this is an important feature for an index developed to represent floods and drought events in a similar probabilistic fashion (Wu et al, 2007;Blain, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations